Levels of thyroid-stimulating and thyroid hormones in pregnant women with obesity and their newborns - O. B. Karelina; N. V. Artymuk; O. A. Tachkova; T. Yu. Marochko; M. N. Surina (Фундаментальная и клиническая медицина)
Aim: To study the level of thyroid-stimulating and thyroid hormones in pregnant women with obesity and their newborns.Materials and Methods. We consecutively recruited 40 pregnant women and their newborns. Blood sampling in pregnant women was carried out at the end of the third trimester 12 hours after the last meal while in newborns it was conducted immediately after birth. Measurement of serum thyroid-stimulating hormone, thyroxine, triiodothyronine, and free thyroxine was performed using chemiluminescent immunoassay.Results. Thyroid disease was significantly more common in pregnant women with obesity. Clinical and latent hypothyroidism in obese pregnant women was observed 1.5-fold more frequently as compared with those having normal body weight. In keeping with these findings, goiter and elevated thyroxine were also more common in obese pregnant women. Newborns from obese women were more often characterized by a transient hypothyroidism in combination with an augmented thyroid-stimulating hormone.Conclusion. Levels of thyroid-stimulating and thyroid hormones in obese pregnant women and their newborns significantly differ from the patients with normal body weight.